PERSEPSI MASYARAKAT TERHADAP KEBERADAAN HUTAN MANGROVE DI KELURAHAN SETAPUK BESAR KECAMATAN SINGKAWANG UTARA KOTA SINGKAWANG - Ayu, Masjuni; Oramahi, H A; Zainal, Sofyan (Universitas Tanjungpura, 2020)
Mangrove forest and the community lived around it are two components that influence each other. The interaction between the two of them is unavoidable because they live in the same environment. Activities, perceptions or actions of the community can affect the sustainability of the existence and the preservation of mangrove forest. This study aims to describe the community perceptions towards mangrove forest and to analyze the correlation that affects community perceptions in Setapuk Besar village towards the level of knowledge, dependence, and cosmopolitanism. The technique of sampling employed in this study is purposive sampling. Based on Slovin formula, a total sample of 74 respondents was obtained. The frequency of community perceptions in Setapuk Besar village on the existence of mangrove forest are: 67 respondents (90.5%) had positive perceptions, 6 respondents (8.1%) had neutral perceptions, and 1 respondent (1.4%) had negative perception. From the results of Kendall tau-b test, the value of Sig 0.000 < 0.01 and Sig 0.028 < 0.05, which indicates that there is a significant correlation between community perceptions with the level of dependence positive correlation (0.419), the correlation strength is moderate. Cosmopolitan level positive correlation (0.190), the correlation strength is low.Â While the value of Sig 0.170 > 0.05, which indicates that there is no significant correlation between community perceptions and the level of knowledge positive correlation coefficient (0.119), the correlation strength is low.Keywords: Community perceptions, mangrove forest, Respondents, Setapuk Besar